Fluorescent Properties of the Amidinophenylporphyrins Interacting with DNA - 王凯 李天 喻发全 郑云满 黄伟国 邝维正 李早英 (Chinese journal of chemistry, 2012)
5,10,15,20-Tetrakis（4-amidinolphenyl）porphyrin, its Zn complex and amidinolphenyl bispophyrin interacting with calf thymus DNA were investigated by fluorescence emission spectra and fluorescence life time measurements were also shown. The binding modes of these compounds were recorded and lifetimes of luminescence were meas- ured as a function of the nature to understand the interaction with DNA. The results suggest those amidinopor-phyrins are promising new photodynamic therapeutic agents.